MAPPING OF COLLABORATIONS AND PUBLICATIONS PATTERN OF SOCIOLOGY RESEARCH IN INDIA BETWEEN 1991 AND 2020: A SCIENTOMETRIC STUDY (LIS TODAY, 2024)
Recent past year, there has been renewed interest in research evaluations and it play  vital role for building reputations of country, organization, institutes and also individual  researcher. Several studies have documented on research evaluation using bibliometric cc  indicator. In this paper, applied bibliometrics indicator for evaluate the research preference  of Sociology research published in India between 1991 and 2020. We accessed Scopus  database and retrieved 2410 publications. The growth of both citations and publications was  not stable overtime period fluctuated. Result showed that, Indian Sociologist scholarly  communion communicated in various format and preferable source of journal was  “Economic and Political Weekly”. More than half of the publications communicated  individually rather than collaboratively. Jawaharlal Nehru University and University of Delhi  standout in top leading organization in terms of contributions. Top most frequently keyword  was “India”. Indian sociologist prefers to collaborate with developing countries such as USA  and UK.
Keywords: Sociology Research; Research Evaluation; Collaborations and Publications Pattern; Sicentometrics; Bibliometrics; Indian Sociology